TI_GERICHTE 52.2007.424 vom 14. März 2008 , Ordine di rimozione di un cartello d'indicazione di direzione per albergo non conforme - TI Tribunale d'appello (2008)
Ordine di rimozione di un cartello d'indicazione di direzione per albergo non conforme